Spatio-Temporal changes in wheat cultivation in Himachal Pradesh: 1990 to 2010 - Kaur, Shivjeet; Thakur, Anuja; Singh Sohal, Kuljeet (National Geographical Journal of India, 2022)
Wheat is a crop of tropical and temperate regions. It is the leading crop in Himachal Pradesh. The main objective of this paper is to reveal the spatio-temporal changes in wheat cultivation in Himachal Pradesh during 1990 to 2010.For this purpose, the present study is divided into three parts. First part reveals the patterns of wheat cultivation for 1990 and 2010.While the second part highlights the changes in wheat cultivation and factors responsible for them. Whereas conclusions are drawn and suggestions are made in part third. From the study, it is found that areas with low altitude, comparatively high temperature, high rainfall, fertile soils comfortable irrigation facilities, etc. have experienced high share of wheat cultivation. In upper Himalayas owing to the popularity of horticulture crops like apple and vegetables, wheat cultivation has suffered. The present paper is based on secondary sources of data. The unit of study is tehsil. Statistical methods are used for deriving the results and cartographic techniques are applied for mapping the results.